Pengaruh Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Sepatu Vans Di E – Commerce - Oktavia Lestari, Tania; Permata Rahmi, Palupi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
The purpose of this study was to determine the effect of brand image and product quality on purchasing decisions for Vans shoe products on e-commerce. Multiple linear regression analysis was used with a research population of 100 respondents. Purchasing decisions are the dependent variable, while brand image and product quality are the independent variables. Data collection was carried out using a questionnaire. Various statistical methods such as partial hypothesis testing, simultaneous analysis, and coefficient of determination were used in this study. The results showed that brand image partially had a negative and insignificant effect on purchasing decisions. Meanwhile, product quality has a positive and significant effect on purchasing decisions. Brand image and product quality simultaneously have a positive and significant effect on purchasing decisions.